Heat tolerance around flowering in wheat identified as a key trait for increased yield potential in Europe under climate change - Stratonovitch, Pierre (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.